The Effectiveness of Teaching Reading by Using Jumbled Pics Stories - Saputri, Lenny Eka; Hadi, Muhamad Sofian (JOLLT Journal of Languages and Language Teaching, 2021)
The aim of the research was to find out if there was any significant improvement on studentâ€™s reading after being taught through Jumbled Pics Stories at 9th grade of students at SMP Al-Fitroh Tangerang. The method used in this research was the quantitative method of pre-experimental design by implementing pre-test and post-test design. In this study, the researcher used 15 students as a sample. The data were corrected by pre-test and post-test as instruments. The result of the study was calculated using t-test. The findings showed that studentâ€™s post-test scores mean (64.33) were higher than pre-test scores mean (71.86). By using t-test, the result of t-table with degrees of freedom (df) 14 reached 7.92. The finding revealed that Jumbled Pics Stories is effective media to improve studentâ€™s reading.Â